Moderating effects of TPCK in biology teachers' professional competence and stem students' subject engagement - Magabilin, Ian Kenneth D. (College of Education, University of the Philippines Diliman, 2019)
The extent of the relationship and interactions between senior high school biology teachers professional competence, TPCK, and STEM students subject engagement is not known. The quantitative, correlational design using hierarchical multiple regression analysis study examined if, and to what extent, a relationship exists between teachers professional competence and students engagement and how this relationship was moderated by TPCK. The Philippine Professional Standards for Teachers, technological, pedagogical content knowledge, and student engagement conceptual framework provided the theoretical foundations and framework for this study. The research questions addressed if there was a significant relationship between teachers competence and each dimension of students engagement and if such relation was moderated by the domains of TPCK. A total of 53 senior high school biology teachers completed the questionnaires on results-based performance management self-assessment tool and Sci-TRACK and a total of 1,855 STEM students completed the Students Course Engagement questionnaires. All respondents came from the 16 Schools Division in NCR. Pearsons r revealed no statistical relationship between teachers professional competence and students engagement. However, correlation analysis on the studied variables showed that there were association between teacher professional competence and pedagogical knowledge (PK), professional competence and pedagogical content knowledge (PCK), professional competence and technological pedagogical knowledge (TPK), professional competence and technological pedagogical content knowledge (TPCK), and professional competence and adoption level (technology). In addition, associations between pedagogical knowledge (PK) and behavioral engagement and between pedagogical content knowledge (PCK) and the combination of cognitive, emotional, and behavioral engagement were noted. Further, there were interactions recorded among the studied variables. The first interaction noted was the path from teacher competence to pedagogical knowledge to behavioral engagement. The second interaction was the path from teacher professional competence to pedagogical content knowledge to combination of cognitive, emotional, and behavioral engagement. Hierarchical moderated multiple regression analysis (MRA) was used to identify the interaction effect to teachers professional competence and TPCK to students subject engagement. The regression analysis showed that there was no moderation effect for any of the domains of TPCK between professional competence and students subject engagement. Recommendations for future research include examining other in-school factors that predict students subject engagement, conducting similar study to a large sample and utilizing qualitative method like classroom observation to thoroughly investigate the relationships that exist among teachers professional competence, TPCK, and students subject engagement. Teacher competence have to be developed for effective teaching through a well-developed teacher preparation program in Teacher Education Institutions (TEIs). Policy makers, school head, and supervisors need to craft and implement learning and development programs that focus on strengthening the skills of teachers through TPCK to enhance their competencies in order for them to effectively deliver the curriculum. Education researchers may look into possible feedback loops among the dimensions of students subject engagement.